Long‐Term Recovery After Severe Sepsis: A Case Study of Rhabdomyolysis and Suspected Remifentanil Withdrawal During ICU Recovery - Hanyang Su; Guozhu Xie (Nursing in Critical Care, 2026)
ABSTRACT Severe sepsis requiring prolonged intensive care and advanced life support may be followed by complex recovery‐phase complications that are difficult to recognise. This case study describes the critical care nursing management and long‐term recovery of a 60‐year‐old woman with severe sepsis who developed rhabdomyolysis during post‐ECMO recovery and suspected remifentanil withdrawal during ventilator weaning. Nursing care focused on continuous assessment, early recognition of complications, renal protection, symptom monitoring during opioid tapering, nutrition support, family communication and staged rehabilitation. After 62 days of intensive care, the patient regained independent ambulation and was successfully weaned from remifentanil. At follow‐up in February 2026, she was living independently without readmission, with stable renal function, PaO 2 /FiO 2 ratio of 360 mmHg, muscle strength of 4–5/5 and a Barthel Index score of 90/100. This case highlights the role of recovery‐oriented critical care nursing beyond ICU survival.